In-situ visualization of sound-induced otolith motion using hard X-ray phase contrast imaging - Schulz-Mirbach, Tanja (Sci Rep, 2018)
Regarding the basics of ear structure-function relationships in fish, the actual motion of the solid otolith relative to the underlying sensory epithelium has rarely been investigated. Otolith motion has been characterized based on a few experimental studies and on approaches using mathematical modeling, which have yielded partially conflicting results. Those studies either predicted a simple back-and-forth motion of the otolith or a shape-dependent, more complex motion. Our study was designed to develop and test a new set-up to generate experimental data on fish otolith motion in-situ. Investigating the basic parameters of otolith motion requires an approach with high spatial and temporal resolution. We therefore used hard X-ray phase contrast imaging (XPCI). We compared two anatomically well-studied cichlid species, Steatocranus tinanti and Etroplus maculatus, which, among other features, differ in the 3D shape of their otoliths. In a water-filled tank, we presented a pure tone of 200 Hz to 1) isolated otoliths embedded in agarose serving as a simple model or 2) to a fish (otoliths in-situ). Our new set-up successfully visualized the motion of otoliths in-situ and therefore paves the way for future studies evaluating the principles of otolith motion.